Enhancing Learning Through Play : A developmental perspective for early years settings - Macintyre, Christine, 1938- (London : David Fulton, 2001)
By highlighting the learning potential with different play activities, this book shows how play can complement and enhance the social, emotional, perceptual motor and intellectual development of children in their early years.
Includes bibliographical references (p. 111-114) and index.
Keywords: Play; Early childhood education -- Great Britain; Child development; Education